RESURJENSI WERENG BATANG COKELAT AKIBAT APLIKASI INSEKTISIDA ABAMEKTIN - , NOVA LAILI WISUDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Low concentrations of insecticide often stimulate the insects fecundity that would contribute to resurgence. Nilaparvata lugens is the primary pest in rice and this insect has been frequently reported for resurgence after application of several different insecticides. Abamectin belongs to the family of macrocyclic lactones and it is intensively being used to control N. lugens. This insecticide is also known that application at sublethal concentrations can alter the plant nutrition composition. This research was conducted to determine the effect of abamectin application on rice plant nutrition and N. lugens resurgence. N. lugens used in this experiment was the laboratory-adapted population and susceptible to insecticides. The rice variety used was Situ Bagendit. The insecticide concentrations were 18 (the recommended field application)